Burnout and technostress during the COVID-19 pandemic: the perception of higher education teachers and researchers - Marrinhas, Daniel; Santos, Vanda; Salvado, Catarina; Pedrosa, Daniela; Pereira, Anabela (Frontiers in Education, 2023)
The COVID-19 pandemic had significant impacts on working conditions of teachers and researchers, jeopardizing their mental health and increasing the risk of burnout and technostress. The purpose of this study was to assess the experiences of burnout and technostress among higher education teachers and researchers during the pandemic. A total of 333 participants responded to an assessment protocol which included the Burnout Assessment Tool (BAT) and the Computer-Induced Distress scale (CID). The protocol was disclosed via email during a 2-month period and data was collected using Microsoft Forms. The results verified the prevalence of burnout and technostress, confirmed the existence of significant differences between sociodemographic groups and found correlations between the BAT and the CID. The findings indicate moderate levels of burnout and technostress, suggest several influence factors to their development, and show a relationship between burnout and technostress. Implications of this study are discussed, reenforcing education, training, decent work, and wellbeing as the main challenges for human being to support a sustainable development. As there are few studies in this area, there is a need to pay more attention to mental health issues and needs among teachers and researchers, such the ones related to burnout and technostress, to promote their well-being, as well as to education for sustainable development.